Association between domestic violence and women's quality of life - Kerle Dayana Tavares de Lucena; Rodrigo Pinheiro de Toledo Vianna; João Agnaldo do Nascimento; Hemílio Fernandes Coelho Campos; Elaine Cristina Tôrres Oliveira
ABSTRACT Objective: to analyze the association between domestic violence against women and quality of life. Method: a cross-sectional population-based household survey conducted with women 18 years and older, using a stratified sample by neighborhoods. For analysis, prevalence of domestic violence and quality of life index was verified and logistic regression was used to determine associations, with a significance level of 5%. Results: 424 women who had a prevalence of domestic violence of 54.4% and a quality of life index of 61.59 participated in this study. It was verified, through logistic regression, that domestic violence is associated with women's quality of life (p=0,017). The observed variables that influence the occurrence of domestic violence were in the social relations domain (p=0,000), provision of medical treatment for women (p=0,019) and safety (p=0,006). Conclusion: the study confirmed the evidence of an association between domestic violence against women and quality of life, a situation that reaffirms the importance of constructing public policies focused on gender emancipation.